Gambaran Persepsi Tenaga Kesehatan Dalam Penggunaan RME di RSUD Singaparna Medika Citrautama - Ulfa Fauziah; Fery Fadly (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Information technology system application has been carried out in various fields, including in the health sector. One of which is the use of electronic medical records in various health facilities. However, in Indonesia, this application has not been evenly carried out, and in health facilities that does implement it, its implementation has not been maximized, especially in hospitals. There are still many obstacles in its use in real life. Understanding health workers’ perception in the use of electronic medical records plays an important role in its successful implementation. This study aims to see the general perspective of health workers’ perception in the use of electronic medical records in RSUD Singaparna Medika Citrautama (Singaparna Medika Citrautama Public Hospital). This study used quantitative research methods with an analytic research design, with a sample size of 80 health workers that are gathered using Proportionate Stratified Random Sampling. Results showed that in general, the perception of health workers’ who use electronic medical records at RSUD Singaparna Medika Citrautama show a good perception, as indicated with a 95,11% (Strongly agree) index percentage of the performace expectation dimension, a 92,5% (Strongly agree) index percentage of the effort expectation dimension, a 90,58% (Strongly agree) index percentage of the social influence dimension, and a 83.57% (Moderately agree) of the facilitating conditions dimension